Creation of a Multimodal Telemedicine Curriculum for Preclinical Medical Students - Marguerite Costich; Joseph Picoraro; Theresa Scott; Beth Barron; Evin Feldman; Suzanne Friedman (MedEdPORTAL)
Introduction In 2020, the AAMC created telemedicine competencies to guide curriculum and assessment development. Most available curricula are designed for clinical medical students or graduate trainees, and few offer opportunities for individualized, timely feedback and participation in pediatric simulated encounters. Methods We designed a hybrid curriculum to provide preclinical medical students with the knowledge and skills necessary to perform telemedicine encounters. The curriculum incorporated both an asynchronous online learning module and a synchronous skills workshop (1.5–2 hours) with real-time feedback from both simulated participants (SPs) and faculty. Both qualitative and quantitative methodology was used in curriculum evaluation. We invited faculty members to participate in semi-structured interviews to explore their experiences with the curriculum. We surveyed students on both general perceptions of the online module and SP workshops and knowledge on telemedicine gained from participation. Student telemedicine skills checklists from the SP workshops were also reviewed. Results Approximately 140 students participated in the curriculum each year in 2021 and 2022. Students demonstrated significant increases in self-reported knowledge in telemedicine after the curriculum (p < .001), and students were satisfied with curriculum content and design. Themes that emerged from faculty semi-structured interviews related to perceptions of the curriculum. Areas of strength on the telemedicine student skills checklist were establishing rapport, optimizing presence on video, and demonstrating empathy in a virtual space. Discussion As telemedicine becomes integral to clinical practice, early training is essential. This telemedicine curriculum for preclinical medical students provides a comprehensive multimodal foundation in virtual communication and physical examination skills.